Validation of the Hungarian version of the Yale Food Addiction Scale 2.0 (YFAS 2.0) - Afework Tsegaye; Zsófia Németh; Eszter Kotyuk; Virág Scheller; Klaudia Szabó; Orsolya Pachner; Renáta Cserjési; Zsolt Demetrovics; H.N. Alexander Logemann (Addictive Behaviors Reports)
Background: The Yale Food Addiction Scale 2.0 (YFAS 2.0) was recently updated to assess food addiction according to the DSM-5 criteria for substance-related and addictive disorders. This study aimed to validating the YFAS 2.0 on the Hungarian sample. Method: A cross-sectional descriptive study was conducted with a sample of 605 participants. The instruments used for data collection included the YFAS 2.0, Three-Factor Eating Questionnaire Revised 21-Items (TFEQ-R21), The 21-item Barratt Impulsiveness Scale Revised (BIS-R-21), Depression, Anxiety and Stress Scale (DASS-21). The factor structure, internal consistency and convergent validity of the Hungarian version of the YFAS 2.0 were evaluated. Results: Proportion to the current sample Food Addiction was 18.5 %. Confirmatory factor analysis supported a good fit for the single-factor model. The YFAS 2.0 symptom count demonstrated a positive correlation with TFEQ-R-21 subscales, ranging from 0.12 to 0.54, with BIS-R-21 subscales ranging from 0.24 to 0.49, and with DASS-21 subscales ranging from 0.41 to 0.50. The H-YFAS 2.0 food addiction severity was significantly associated with TFEQ-R-21, BIS-R-21, and DASS-21 subscales of the scales. All of which were statistically significant (p < 0.001), indicating acceptable convergent validity. Conclusion: The Hungarian version of the YFAS 2.0 has been validated in a nonclinical sample, demonstrating its utility as an effective tool for screening food addiction.